Predisposing Factors and Pattern of Gingival Recession Among the Patients Attending the Periodontal Department at Dhaka Dental College: An Observational Study (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Gingival recession is defined as the displacement of the gingival margin apical to cemento-enamel junction leading to exposure of the root’s surfaces of the teeth. Thus, it creates an aesthetic problem as well as hypersensitivity of the tooth and roots caries. Objectives of this study were to explore the distributions, the severity and contributory factors of the gingival recession. Materials and methods: In this study, we studied 60 patients aged between 14 to 70 years of both sex. The presence of gingival recessions were recorded using Miller`s classification of gingival recession. Chi- square test and Students paired t-test was done to assess the association between dependent and independent variables. Results: In this study, the most frequent gingival recession was found within the age group 20-30. Higher frequency of gingival recession was seen in male (68.33%) compared to female (31.67%). Again, Miller’s class one was the most frequent recession. As a whole, anterior teeth (38%) showed more recession than premolars (25%) and molars (37%) respectively. Plaque accumulation (85%) was found as the most contributory factor for gingival recession. Length of gum recession, before and after scaling, not extending beyond the mucogingival margin were statistically correlated and found significant. Conclusion: The information found in this study would probably help in adopting long term strategies to prevent the occurrence of gingival recession.JCMCTA 2018 ; 29 (1) : 63-67